Research on Solenoid Valve Plunger Detection System for Automotive Powertrain Applications - Dimitrov, Borislav; Abbasian, Mohammadali (Journal of Electronics and Electrical Engineering, 2025)
This research presents a design for a power supply system specialized in supplying a solenoid electromechanical system, a crucial component in automotive applications including electric vehicles. To meet Functional Safety (FS) requirements, plunger position monitoring—a key feature mandated by functional safety standards—is implemented using a microprocessor system. The proposed system topology aims to achieve Quality Management (QM) for the monitored electromechanical system at ASIL B or ASIL D (Automotive Safety Integrity Level), contributing to advancements in the automotive industry. The developed monitoring system incorporates two independent plunger detection mechanisms based on current measurement, calculation, and position estimation. The proposed power supply utilizes a modified Forward converter, with structural and methodological adaptations tailored to the solenoid’s characteristics. The results are analyzed and supported by experimental verification, demonstrating the system’s potential for industry application.